Henoch-Schönlein Purpura Presenting in Association With Neuroblastoma: A Case Report - Alfath, Zineb; Ferdjallah, Asmaa; Greengard, Emily; Askari, Sabeen K.; Sadak, Karim T.; Correll, Colleen K. (Frontiers in Pediatrics, 2020)
Henoch-Schönlein purpura (HSP) is a common systemic vasculitis affecting children. It is managed in the outpatient setting and rarely associated with malignancy. We present a case of neuroblastoma in a 7-year-old boy diagnosed after suspected HSP. Our case highlights the importance of maintaining a broad differential diagnosis in children with atypical HSP and performing a skin biopsy with immunofluorescence when a rash is present.